Structured Robust Control for the Aerodynamic Steering of Reusable Rockets. Issue 25 (2022) - Sagliano, Marco; Farì, Stefano; Hernandéz, José Macés; Heidecker, Ansgar; Garrido, José; Winter, Matthias; Seelbinder, David; Schlotterer, Markus; Woicke, Svenja; Dumont, Etienne
Abstract: This paper investigates the use of structured H∞ control for the aerodynamic descent phase of a reusable rocket. A unified control strategy for attitude and position is proposed and verified. The architecture of the controller, together with the observed performance are discussed. Results are presented for CALLISTO, a reusable rocket demonstrator jointly developed by DLR, JAXA and CNES.